A Hybrid Random Forest based Support Vector Machine Classification Supplemented by Boosting (Global Journal of Computer Science and Technology, 2014)
This paper presents an approach to classify remote sensed data using a hybrid classifier. Random forest, Support Vector machines and boosting methods are used to build the said hybrid classifier. The central idea is to subdivide the input data set into smaller subsets and classify individual subsets. The individual subset classification is done using support vector machines classifier. Boosting is used at each subset to evaluate the learning by using a weight factor for every data item in the data set. The weight factor is updated based on classification accuracy. Later the final outcome for the complete data set is computed by implementing a majority voting mechanism to the individual subset classification outcomes.
Keywords: boosting; classification; data mining; random forest; remote sensed data; support vector machine